Simultaneous determination of acetamiprid and 6‐chloronicotinic acid in environmental samples by using ion chromatography hyphenated to online photoinduced fluorescence detector. Issue 20 (11th September 2020) - Subhani, Qamar; Muhammad, Nadeem; Huang, Zhouman; Asif , Muhammad; Hussain, Irshad; Zahid, Muhammad; Hairong, Cui; Zhu, Yan; Guo, Dandan
Abstract: This study aims to introduce a simple, sensitive, and cost‐effective method for the simultaneous determination of acetamiprid and its main metabolite 6‐chloronicotinic acid in environmental samples by using a nonsuppressed ion chromatography hyphenated with an online postcolumn photoinduced fluorescence detection system. The fluorescence detector wavelengths λex /λem = 257/382 nm was set for up to 6.0 min for acetamiprid, while λex /λem = 231/370 nm programmed for 6‐chloronicotinic acid for the rest of the analysis time. Both samples were treated by applying miniaturized quick, easy, cheap, effective, rugged, and safe method before the separation of analytes on an IonPac ® AS11‐HC column by pumping 40 mM NaOH having minuscule content of acetonitrile (5%, v/v) as an eluent. Both intrinsically nonfluorescent analytes were turned‐on by online postcolumn photoinduced derivatization, avoiding the need for complex chemical derivatization or addition of a postcolumn extra pump. The developed method was appraised for the analysis of environmental samples, exhibiting excellent linearity (0.050‐10 μg/mL) with a correlation coefficient greater than 0.9993 for both analytes. Whereas, obtained limit of detection (0.025‐0.0072 μg/mL), recoveries (98.02‐116.00%), and inter‐ and intraday precision (≤3.02 %) were satisfactory for both compounds in environmental samples.